Solid Waste Quantity, Composition and Characteristic, and Its Current Management at Elephant Study Center (Surin, Thailand) - Salangam, Atitaya; Phimyon, Jaratsri; Kessada, Panchai; Phuengphai, Pongthipun; Thanomsit, Chutima; Jamnongkan, Tongsai; Tongnunui, Sampan; Wattanakornsiri, Amnuay (Asian Health, Science and Technology Reports, 2019)
The main aspects of solid waste management in an area are the quantities, compositions and characteristics, as well as its current management situations. Elephant Study Center (or Elephant Village), well known by Thais and foreigners, presently lacks of data on generated solid waste quantities, compositions and characteristics, including its management. This study investigated the quantities using purposive sampling of solid waste containers, the compositions according ASTM D 5231-92 standard, and some characteristics, i.e. bulk density, moisture content and total solid, using weighting and weight differences. In addition, the current solid waste management problems, community participation levels, and recommendations were studied by using questionnaire and interviews. The results found that the average amount of solid waste was 138.44±15.42 kg/d. The compositions were 17.50%, 47.20%, 30.17% and 5.13% of organic waste, general waste, recyclable waste and other wastes, respectively. Besides, the characteristics of bulk density, moisture content and total solid were 0.037±.003 kg/l, 57.75±6.85% and 42.44±6.78%, respectively. For the results of current solid waste management, the highest problems were: lack of solid waste management system (4.27±1.16), disarranged disposal (3.78±1.26) and lack of solid waste separation system (3.40±1.34), respectively. The lowest community participation levels in solid waste management were: campaign in using cloth bags, food boxes and baskets for reducing plastic bags and plastic foam (1.82±0.85), problem and cause searching of solid waste management (1.90±0.77) and performance in solid waste management following hygiene or sanitary perspectives (1.91±0.80), respectively, with the overall at lowest level (2.09±0.20). Besides, there was no community participation in solid waste management from interviews. Therefore, community should participate in solid waste management following sanitary solid waste management principle for sustainable management.